Numerical investigation of the deposit effect on GDI injector nozzle flow - Wang, Bo; Badawy, Tawfik; Hutchins, Peter; Tu, Powen; Xu, Hongming; Zhang, Xinyu (Elsevier, 2017)
Injector deposit is a common phenomenon for gasoline direct injection (GDI) engines that greatly affects the spray behavior and consequently the combustion performance and emissions. In this study, the deposit effect on the inner nozzle flow dynamics was numerically investigated. High resolution X-ray scan was performed first to obtain realizable information regarding to the nozzle and deposit morphologies and topology. Simulation was then carried out in the Large Eddy Simulation (LES) framework with cavitation taken into account by a homogeneous equilibrium model (HRM). It was found that the rough surface of deposit would lead to additional cavitation inception inside the counterbore and restrict the flow area, causing losses in the mass flow rate. Deposit inside the counterbore acted as an extension to the inner orifice and restricted the air recirculation, which was believed to be the cause of poor atomization of coked injector spray.